2020
DOI: 10.3390/membranes10070140
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Nanomaterials-Modified Membranes for Improved Membrane Distillation Performance

Abstract: Membrane distillation (MD) is a thermally induced membrane separation process that utilizes vapor pressure variance to permeate the more volatile constituent, typically water as vapor, across a hydrophobic membrane and rejects the less volatile components of the feed. Permeate flux decline, membrane fouling, and wetting are some serious challenges faced in MD operations. Thus, in recent years, various studies have been carried out on the modification of these MD membranes by incorporating nanomaterials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 136 publications
(150 reference statements)
1
27
0
Order By: Relevance
“…Various methods have been extensively employed for the POPs removal in wastewater such as flocculation/coagulation [6], adsorption [5,7], photocatalytic [8,9], Fenton-like catalysts [10,11], membrane separation [12,13], and reverse osmosis [14]. Among these methods, adsorption, catalytic degradation, and membrane separation are promising techniques for eliminating harmful pollutants from wastewater due to their low cost and simple process [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been extensively employed for the POPs removal in wastewater such as flocculation/coagulation [6], adsorption [5,7], photocatalytic [8,9], Fenton-like catalysts [10,11], membrane separation [12,13], and reverse osmosis [14]. Among these methods, adsorption, catalytic degradation, and membrane separation are promising techniques for eliminating harmful pollutants from wastewater due to their low cost and simple process [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As has been indicated by Yao et al [4], key factors influencing fouling and wetting in the MD process are classified as: membrane surface properties, process parameters and feed characteristics. An increasing number of studies have found that reducing of the fouling intensity can be achieved by various methods of modifying the surface properties of the membranes [13][14][15][16][17][18][19]. For example, it has been demonstrated [20,21] that fouling caused by hydrophobic compounds present in the feed can be successfully limited by improving the membrane's surface hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…The main factors that limit its applications in industrial fields are scale and stability, similar to many emerging technologies. The majority of the studies on MD are focused on the development of novel porous membranes for MD applications [8][9][10][11][12], the transmembrane transport analysis in microscale [13][14][15][16][17], the configurations and their related performance [18][19][20]. The MD performance criteria usually include the permeate flux, salt rejection, specific energy consumption, scaling resistance and operating stability.…”
Section: Introductionmentioning
confidence: 99%